Who You Know - Fisher, Julia; Fisher, Daniel (Ascent Audio, 2019)
Relationships matter. Who You Know explores this simple idea to give teachers and school administrators a fresh perspective on how to break the pattern of inequality in American classrooms. It reveals how schools can invest in the power of relationships to increase social mobility for their students. Discussions about inequality often focus on achievement gaps. But opportunity is about more than just test scores. Opportunity gaps are a function of not just what students know, but who they know. This book explores the central role that relationships play in young people's lives, and provides guidance for a path forward. Schools can: - Integrate student support models that increase access to caring adults in students' lives - Invest in learning models that strengthen teacher-student relationships - Deploy emerging technologies that expand students' networks to experts and mentors from around world Exploring the latest tools, data, and real-world examples, this book provides evidence-based guidance for educators looking to level the playing field and expert analysis on how policymakers and entrepreneurs can help.